Matrilineal evidence for a demographic expansion, low diversity and lack of phylogeographic structure in the Atlantic forest endemic Greenish Schiffornis Schiffornis virescens (Aves: Tityridae) - Cabanne, Gustavo Sebastián (2013)
Abstract Studies of Atlantic forest (AF) organisms sug- gest that the historical dynamics of the forest cover pro- duced demographically stable populations in its central region and unstable populations in the southern regions. We studied the mitochondrial phylogeographic structure of an AF passerine, the Greenish Schiffornis Schiffornis virescens (Tityridae), and evaluated questions related to the history of the AF. We analyzed cytochrome b and control region sequences of the mitochondrial genome by traditional phylogenetic and population genetic methods based on summary statistics. In addition, we used coalescent simu- lations to evaluate specific models of evolution of the populations of S. virescens. The results did not support phylogeographic partitions of the genetic variability of S. virescens. The overall Ust was = 0.32 and gene flow between regions was moderate to high. The analyses sug- gested that the total population of S. virescens suffered a bottleneck followed by a demographic expansion in the late Pleistocene. The bottleneck might have contributed to the extinction of intraspecific lineages, and hence to the observed lack of a strong phylogeographic pattern and low genetic diversity. Our results suggest that some AF taxa have had all their populations similarly affected by the recent history of the biome, contrary to what has been revealed from most of the other phylogeographic studies in the region and as suggested by a model of AF refuges (the Carnaval–Moritz model). We suggest that the response of organisms to common histories may be idiosyncratic, and predictions about the history of the biome should take into account ecological characteristics and distribution of each specific taxa.